3D printing of silver-doped polycaprolactone-poly(propylene succinate) composite scaffolds for skin tissue engineering. (14th April 2020) - Afghah, Ferdows; Ullah, Mohib; Seyyed Monfared Zanjani, Jamal; Akkus Sut, Pinar; Sen, Ozlem; Emanet, Melis; Saner Okan, Burcu; Culha, Mustafa; Menceloglu, Yusuf; Yildiz, Mehmet; Koc, Bahattin
Abstract: Scaffold-based tissue engineering approaches have been commonly used for skin regeneration or wound healings caused by diseases or trauma. For an ideal complete healing process, scaffold structures need to meet the criteria of biocompatibility, biodegradability, and antimicrobial properties, as well as to provide geometrical necessities for the regeneration of damaged tissue. In this study, design, synthesis and characterization of a three dimensional (3D) printable copolymer based on polycaprolactone-block-poly(1, 3-propylene succinate) (PCL-PPSu) including anti-microbial silver particles is presented. 3D printing of PCL-PPSu copolymers provided a lower processing temperature compared to neat PCL, hence, inclusion of temperature-sensitive bioactive reagents into the developed copolymer could be realized. In addition, 3D printed block copolymer showed an enhanced hydrolytic and enzymatic degradation behavior. Cell viability and cytotoxicity of the developed copolymer were evaluated by using human dermal fibroblast (HDF) cells. The addition of silver nitrate within the polymer matrix resulted in a significant decrease in the adhesion of different types of microorganisms on the scaffold without inducing any cytotoxicity on HDF cells in vitro . The results suggested that 3D printed PCL-PPSu scaffolds containing anti-microbial silver particles could be considered as a promising biomaterial for emerging skin regenerative therapies, in the light of its adaptability to 3D printing technology, low-processing temperature, enhanced degradation behavior and antimicrobial properties.